Uplift Behavior of Belled Short Piles in Weathered Sandstone. (16th September 2018) - Yang, Bai; Ma, Jianlin; Chen, Wenlong; Yang, Yanxin
Abstract : Field pull out test results of 500 kV double-circuit line of Luping-Fule are presented in this paper to investigate the uplift bearing behavior of rock-socketed belled short piles. A calculation model of rock-socketed belled short pile has been proposed. During the initial stage of loading test, uplift load is shared by even section and bell of the pile, and the bell continues to bear uplift load after the lateral resistance of even section pile reaches the limit. A different performance has been found on the case of long belled pile. At the ultimate state, the uplift resistance provided by bell accounts for about 54.9% and 34.7% of the total uplift capacity for the 6.0 m long and 7.0 m long piles, respectively. Increasing pile length has been found to noticeably increase the ultimate uplift bearing capacity, while it has less effect on the displacement of pile top. The uplift capacity of even section pile is associated with the shear strength of rock mass around the pile, and the test results demonstrate that the ultimate resistance can be equal to the shear strength. The calculation method proposed in this paper is proven to be able to accurately predict the ultimate uplift bearing capacity of the rock-socketed belled short piles.